Physical activity during pregnancy is associated with a lower prevalence of gestational diabetes mellitus in Vietnam - Nguyen, C.; Pham, N.; Lee, Andy; Nguyen, P.; Chu, T.; Ha, A.; Duong, D.; Duong, T.; Binns, Colin (2018)
© 2018 Springer-Verlag Italia S.r.l., part of Springer Nature Aims: To assess the association between physical activity (PA) during pregnancy and the prevalence of gestational diabetes mellitus (GDM) accounting for sitting time. Methods: The study used data from a cohort study of 2030 pregnant women in Vietnam. Women were recruited from six hospitals in Ha Noi, Hai Phong, and Ho Chi Minh City. Baseline measurements including PA and GDM were taken at 24–28 weeks of gestation. PA was assessed during the past 3 months before the interview using the interviewer-administered Pregnancy Physical Activity Questionnaire. GDM was diagnosed at 24–28 weeks of gestation using the 2013 World Health Organization criteria. Results: 1987 out of 2030 pregnant women were included in the final analysis, of which 432 had GDM (21.7%). Women undertaking the highest level (upper tertile) of PA during pregnancy appeared to have a lower risk of GDM [odds ratio (OR) 0.70, 95% confidence interval (CI) 0.53–0.94, Ptrend0.017] when compared to those at the lowest tertile of PA. Similarly, women with increased levels of moderate-intensive activity and household/caregiving activity during pregnancy were associated with reduced risks of GDM (OR 0.66, 95% CI 0.50–0.86, Ptrend0.002 and OR 0.72, 95% CI 0.55–0.95, Ptrend0.020, respectively). These apparent inverse associations were not attenuated by their sitting time. There were no significant associations between sitting time, light-intensity activity, vigorous-intensity activity, occupation, sports/exercise, commuting, or meeting exercise guidelines and GDM risk. Conclusions: High levels of PA, particularly moderate-intensity and household/caregiving activities during pregnancy were associated with a lower prevalence of GDM independent of sitting time.